Uprawnienia mieszkańców jednostek samorządu terytorialnego w zakresie dostępu do informacji publicznej - Cern, Grażyna; Bojar-Fijałkowski, Tomasz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
The text tries to answer a question which information is to be recognized as public information, whereby local communities and/or self-government should share the information if requested by citizens. More than that, the text aims to present the rule of disclosure and access to public information as well as ways of implementing them in local governments. It is also worth to debate when public information is recognized as processed and what an internal document is, if it is also recognized as public information. In consequence, a requirement to prove a special social interest, when applying for the processed information, also becomes a significant issue. Finally, authors raise a question what to do when an organ which is obliged, in this case a self-government unit, rejects an access to such information or when one deals with its inaction in that field. Due to a generality of those regulations and lack of legal definitions of many instruments, including the term of public information, it is necessary to present a doctrine and judgments on that issue.
Rights of members of local government units in access to public information
Keywords: local government unit; citizens; public information; limits in access to public information; disclosure